2016
DOI: 10.1161/jaha.116.004213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Ablation of Atrial Fibrillation on the Progression of Tricuspid Regurgitation and Right‐Sided Heart Remodeling After Mitral‐Valve Surgery: A Propensity‐Score Matching Analysis

Abstract: BackgroundThis study assessed the role of surgical ablation for atrial fibrillation (AF) in decreasing tricuspid regurgitation (TR) and right‐sided heart remodeling in patients after mitral valve procedure.Methods and ResultsBetween 1994 and 2014, 1568 consecutive patients with AF undergoing mitral valve procedure were identified. In 26.0% (n=408), surgical ablation of AF was used. Propensity‐score matching (PSM) was performed on the basis of 41 known perioperative risk variables. Survival, reoperation, stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Others have found a substantial increase in retrieval rates (up to 90%) when certain follow-up strategies were implemented after filter placement. [19][20][21][22][23] These include use of multidisciplinary teams, standardized protocols, patient education, automated reminder, or referral systems and creation of dedicated VCF clinics. Such a standardized, structured follow-up program was not utilized at our institution during the study period, and despite limited data showing efficacy in increasing filter retrieval, a specific recommendation is not present in current guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have found a substantial increase in retrieval rates (up to 90%) when certain follow-up strategies were implemented after filter placement. [19][20][21][22][23] These include use of multidisciplinary teams, standardized protocols, patient education, automated reminder, or referral systems and creation of dedicated VCF clinics. Such a standardized, structured follow-up program was not utilized at our institution during the study period, and despite limited data showing efficacy in increasing filter retrieval, a specific recommendation is not present in current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have reported that the incidence of these complications increases with prolonged use of filters 13 and a decision analysis study found that the risk/benefit profile favors filter removal between 29 and 54 days. 14 Despite an increase in VCF retrieval in the United States following the 2010 FDA advisory statement [15][16][17][18] and several studies reporting retrieval rates of up to 85% following the implementation of structured follow-up programs, [19][20][21][22][23] at a national level, VCF retrieval rates remain low with an estimated average of 25 to 30% at 1 year. 13,16,18,24,25 European retrieval rates tend to be higher but vary from approximately 40 9,26 to 77% at 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with persistent AF develop tricuspid annular dilation, especially along the posterior border of the valve, resulting in TR 10 . Conversely, surgical ablation of AF has been associated with improved cardiac function and interruption of TR progression in patients who are undergoing surgical correction of mitral regurgitation 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, left-sided heart disease with AF was associated with TR progression as well as right-sided heart remodeling. These changes were alleviated by surgical ablation (Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%